INTAKE OF NUTRIENTS, STUNTING AND ANEMIA IN THE ELEMENTARY SCHOOL CHILDREN IN TRADISIONAL GOLD MINING POBOYA, PALU - Bohari, Bohari; Rahman, Nurdin; Indriany, Indriany (Tadulako University, 2017)
Background & Objective: School-aged children are a group of children who are vulnerable to unbalanced nutritional intake so that the risk of high rates of growth failure in children. To analyze the correlation of protein, essential amino acids, folic acid and iron intake with z-score height according to age and hemoglobin level. Material and Method: A quantitative research using cross-sectional research design. The population is all elementary school students class I - V at SDN Poboya is 220 students. The sample size obtained by Slovin formula calculation is 69 students. Data of protein, amino acids, folic acid and iron intake were measured using SQ-FFQ questionnaire. Stunting is measured using a height measuring instrument and WHO Anthro application, hemoglobin levels using the GCHb EasyTouch tool. Analysis data of univariate and bivariate. Results: Average protein intake (66.3 ± 1.6 g), amino acid (isoleu-cine = 3.1 ± 0.7; leucine = 5.3 ± 1.3; lysine = 4.4 ± 1.2; methio-nine = 1.5 ± 0.4), iron (7.7 ± 2.1), and folic acid (150.6 ± 45.4). The incidence of stunting is 15.9% and anemia is 33.3%. Intake of proteins, amino acids, iron, and folic acid had no significant correlation with the value of Z-Score Height According to Age (p> 0.05) whereas with hemoglobin levels have a significant correlation (p < 0,05). Conclusion: Intake of nutrients that are still less than the AKG in children are amino acids, folic acid and iron. The intake of nutrients that correlated positively with hemoglobin levels were proteins, amino acids, folic acid, and iron